Políticas laborales y su incidencia en la prevención del COVID 19 en el Hospital de Apoyo Chepén, La Libertad, 2020 - Delgado Paredes, Annie Kristell Del Rocio (2022)
The objective of the study was to: determine to what extent labor policies affect the prevention of Covid-19 of the staff of the Hospital de Apoyo, Chepén, La Libertad 2020. The research is of a descriptive correlational level, of non-experimental design, with a focus quantitative basic type and cross-sectional. The sample consisted of 147 between administrative and assistance workers. Data collection was done through the survey technique, therefore the questionnaire of questions was used as an instrument. According to the results obtained, the level of compliance with labor policies in the Support Hospital, Chepén was regular in 38%, as for the level of prevention of Covid-19 of the Support Hospital staff, it is low in 59%. Finally, the statistical test shows a high mean positive relationship, since the correlation coefficient is 0.675; squared, it shows that variable I has a 45% effect on variable II. At the same time, we can conclude that the research hypothesis is accepted where it mentions that labor policies have a significant impact on the prevention of Covid-19 of the staff of the Hospital de Apoyo, Chepén, La Libertad 2020.